NUMERICAL STUDIES OF THE DYNAMIC IMPACT OF THE BLAST WAVE ON PROTECTIVE STRUCTURES - Polyakov, Anton; Lapenko, Oleksandr (Theory and practice of design, 2025)
Purpose. The study is aimed at numerical modeling of the dynamic impact of a blast wave on protective structures. The main goal is to compare three approaches to calculating blast loads — the analytical method, the empirical Kingery-Bulmash model, and modeling in the Ansys AUTODYN software environment — in order to study different modeling techniques and analyze the behavior of structures under the influence of an explosion. Methodology. The work used three methods of numerical analysis: (1) analytical calculation according to the method described in scientific sources, (2) an online calculator based on the empirical Kingery-Bulmash equations, and (3) modeling in Ansys AUTODYN using the RHT and JWL EOS material models. For each method, calculation models were built, simulations were performed, and data on pressure, momentum, front velocity, and duration of the positive phase were collected. Results. Detailed calculations of the blast wave parameters at different distances from the epicenter were obtained for each method. It was found that the largest discrepancies between the methods are observed in the estimates of the reflected pressure (up to 91.5%) and the duration of the positive phase (up to 120%). Scientific novelty. For the first time, a systematic comparison of three methods for numerical modeling of the impact of an explosion on a reinforced concrete structure was performed with an assessment of the discrepancies between the results and an analysis of the causes of these deviations. A method for comparing each approach based on the relative deviation from the average value was proposed. Practical relevance. The results of the study are useful for engineers and designers of protective structures. It was concluded that the use of AUTODYN is appropriate for accurate analysis of complex objects, while analytical methods can be used at the previous stages.